2010
DOI: 10.2214/ajr.09.3534
|View full text |Cite
|
Sign up to set email alerts
|

Apparent Diffusion Coefficient Values for Discriminating Benign and Malignant Breast MRI Lesions: Effects of Lesion Type and Size

Abstract: Diffusion-weighted MRI shows promise in differentiation of benign and malignant masses and lesions with nonmasslike enhancement found at breast MRI and is not affected by lesion size. However, ADC measurements may be more useful for discriminating masses than for discriminating lesions with nonmasslike enhancement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
121
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(138 citation statements)
references
References 28 publications
14
121
3
Order By: Relevance
“…A previous study by Partridge et al (32) reported that for the same b value, the diagnostic performance of ADC was lower in NME lesions compared with masses larger than 1 cm (34). Another study carried out by the same researchers also suggested that ADC measurements may be more valuable for distinction of masses than for differentiating lesions with NME (35). We also found that there was no statistical difference when considering NME internal enhancement and NME distribution in verifying malignancy.…”
Section: Discussionsupporting
confidence: 66%
“…A previous study by Partridge et al (32) reported that for the same b value, the diagnostic performance of ADC was lower in NME lesions compared with masses larger than 1 cm (34). Another study carried out by the same researchers also suggested that ADC measurements may be more valuable for distinction of masses than for differentiating lesions with NME (35). We also found that there was no statistical difference when considering NME internal enhancement and NME distribution in verifying malignancy.…”
Section: Discussionsupporting
confidence: 66%
“…Breast MRI is an established supplemental technique to mammography and ultrasonography for evaluation of suspicious breast lesions. Diffusion-weighted MRI (DWI) has recently been integrated into the standard breast MRI for discrimination of benign and malignant breast lesions obtained with dynamic contrast-enhanced MRI [1][2][3][4][5][6][7][8][9][10][11][12][13]. DWI is a non-invasive technique that represents the biological character of the mainly Brownian movement of protons in bulk water molecules in vivo.…”
mentioning
confidence: 99%
“…The ADC values of lesion groups and normal fibroglandular tissue derived from the literature and the ADC values we identified in our study are given in Table 3 for comparison (7,8,(17)(18)(19)(20)(21)(22)(23)(24) . As seen, although there are slight differences between the ADC values of various studies, statistically significant differences have been identified between groups in all studies.…”
Section: Resultsmentioning
confidence: 99%
“…We also observed a statistically significant difference between the groups (except the difference between normal tissue and benign lesions), thus our study is consistent with literature data. Guo et al (7) Rubesova et al (17) Woodhams et al (18) Kuroki et al (19) Hatakenaka et al (8) Sinha and Sinha (20) Marini et al (21) Luo et al (22) Patridge et al (23) Arantes Pereira et. al.…”
Section: Resultsmentioning
confidence: 99%